Sadder but Wiser: The Role of SARS Imprinting and Firms’ Recovery During the COVID-19 Pandemic - Yao, Haitang; Wang, Jiayang; Bo, Qingwen; Li, Mingliang (Frontiers in Psychology, 2022)
Our study provides a new research perspective on firms’ recovery during the COVID-19 pandemic, i.e., can similar events experienced by firms in the past have an imprinting effect on the improvement of firm’s recovery? We focus on firms’ Severe Acute Respiratory Syndromes (SARS) imprints. Based on four quarters of panel data of Chinese A-share listed companies in 2020, our study finds that SARS imprints are positively related to firms’ recovery ability during the COVID-19 pandemic. Meanwhile, if the more severe the SARS pandemic experienced by a firm, the more significant the effect of SARS imprint on the firm’s recovery ability during the COVID-19 pandemic. In addition, the higher the level of digitization of firms during the COVID-19 pandemic, the more it contributed to the enhancing effect of the SARS seal on firm recovery. Our study makes an important theoretical contribution to the recovery literature as well as to imprinting theory, while providing practical guidance for improving the recovery of firms during the COVID-19 pandemic.